Deep Learning to Improve IPAS Motivation and Learning Outcomes for Grade III Students - Maya Krisna Wahyuni; Parji Parji; Sudarmiani Sudarmiani (CV. Edujavare Publishing, 2026)
Deep Learning to Improve IPAS Motivation and Learning Outcomes for Grade III Students